Comparison of Outcome of Myringotomy Alone with Myringotomy and Tympanostomy Tube (Grommet) in Otitis Media with Effusion (OME) - Mudassar Ahmad Khan , Ashar Alamgir , Muhammad Musharaf , Mudassar Ahmad Khan , Ashar Alamgir , Muhammad Musharaf (Journal of Rawalpindi Medical College, 2018)
Background: To compare the outcome of myringotomy alone with myringotomy and tympanostomy tube (grommet) in otitis media with effusion (OME) in terms of improvement in hearing and tympanogram pattern. Methods: In this comparative study 60 patients diagnosed of otitis media with effusion (OME) not responding to medical treatment were included. They were divided in two groups, each of 30 patients. In first group only myringotomy was done. In second group myringotomy with tympanostomy tube insertion was done. The parameters compared were improvement of hearing and improvement in tympanogram pattern. Hearing was assessed by voice test and tuning fork tests (Rinnie’s, Webers). Patients were assessed before surgery, after two weeks, after one month and after three months. Results:Out of 60 patients 39 were males and 21 were females. Age range was from 5 to 15 years with mean age 8 years. In first group there was 48% improvement in hearing and tympanogram pattern after two weeks, 55% improvement after one month and 62% improvement after three months. In second group there was 67% improvement after two weeks, 84% after one month and 95% after three months. One patient (3%) developed post op otorrhoea which was treated by conservative management. Conclusion:Myringotomy with tympanostomy tube insertion has a better outcome in terms of hearing improvement in OME patients as compared to myringotomy alone.